A Note on the Unidentified Animal in the Marisa (Maresha) Tomb Frieze - Miziur-Moździoch, Maja (Polskie Towarzystwo Filologiczne, 2018)
This paper is part of the project “Ptolemy’s Zoo: Animals in Hellenistic Egypt” which has been realised within the “Sonata” programme no 2015/19/D/H53/03032 financed by the Polish National Science Centre (NCN) and conducted in the Polish Classical Association (Societas Philologa Polonorum, PTF)
Keywords: Marisa Tomb; dik-dik